Index microvascular resistance (IMR) in heart transplant patients (IMR-HT study): Study protocol. - Ainhoa Pérez-Guerrero; Jean Paul Vilchez-Tschischke; Luis Almenar Bonet; Jose Luis Diez Gil; Teresa Blasco Peiró; Salvatore Brugaletta; Josep Gomez-Lara; José González Costello; Paula Antuña; Vanesa Alonso Fernández; Fernando Sarnago Cebada; María Dolores García-Cosio; et al. (PLoS ONE)
Background Acute allograft rejection (AAR) is an important cause of morbi mortality in heart transplant (HT) patients, particularly during the first year. Endomyocardial biopsy (EMB) is the "gold standard" to guide post- heart transplantation treatment. However, it is associated with complications that can be potentially serious. The index of microvascular resistance (IMR) is a specific physiological parameter used to assess microvascular function. Invasive coronary assessment has been shown to be both feasible and safe. Detection of coronary microvascular dysfunction (MCD) by IMR may help to identify high risk HT patients. In fact, an increased IMR measured early after HT has been associated with AAR, higher all-cause mortality and adverse cardiac events. A high IMR value early after HT may identify patients at higher risk who require increased surveillance or adjustments in immunosuppressive therapy. Conversely, a low IMR value may support reducing the number of EMBs. Our aim is to evaluate IMR in heart transplant patients within the first year. Changes in management after knowing IMR values and prognostic implications of IMR in a long term follow up will also be assessed. Study design The IMR-HT study (NCT06656065) is a multicenter, prospective study that will include post-HT consecutive stable patients undergoing coronary physiological assessment in the first three months and one year. Cardiac adverse events will be evaluated at one year for up to five years. A clinical management algorithm is proposed: after knowing IMR values the physician will be able to reduce the number of biopsies established in each center protocol or modify immunosuppression therapy. Conclusions IMR values may vary within the first year after heart transplant. IMR assessment will be useful to identify high risk heart transplant patients, leading to possible changes in management and prognosis.